Prediction of primary breast cancer size and T-stage using micro-computed tomography in lumpectomy specimens - Wafa M Sarraj; Rong Tang; Anas L Najjar; Molly Griffin; Anthony H Bui; Alan Zambeli-Ljepovic; Mike Senter-Zapata; Maya Lewin-Berlin; Leopoldo Fernandez; Juliette Buckley; Amy Ly; Elena Brachtel; et al. (Elsevier, 2015)
Background: Histopathology is the only accepted method to measure and stage the breast tumor size. However, there is a need to find another method to measure and stage the tumor size when the pathological assessment is not available. Micro-computed tomography. (micro-CT) has the ability to measure tumor in three dimensions in an intact lumpectomy specimen. In this study, we aimed to determine the accuracy of micro-CT to measure and stage the primary tumor size in breast lumpectomy specimens, as compared to the histopathology. Materials and Methods: Seventy-two women who underwent lumpectomy surgery at the Massachusetts General Hospital Department of Surgery from June 2011 to September 2011, and from August 2013 to December 2013 participated in this study. The lumpectomy specimens were scanned using micro-CT followed by routine pathological processing. The maximum dimension of the invasive breast tumor was obtained from the micro-CT image and was compared to the corresponding pathology report for each subject. Results: The invasive tumor size measurement by micro-CT was underestimated in 24. cases. (33%), overestimated in 37. cases. (51%), and matched it exactly in 11. cases. (15%) compared to the histopathology measurement for all the cases. However, micro-CT T.stage classification differed from histopathology in only 11. (15.2%) with 6. cases. (8.3%) classified as a higher stage by micro-CT, and 5. cases. (6.9%) classified as lower compared to histopathology. In addition, micro-CT demonstrated a statically significant strong agreement (κ =0.6, P < 0.05) with pathological tumor size and staging for invasive ductal carcinoma. (IDC) group. In contrast, there was no agreement. (κ = .2, P = 0.67) between micro-CT and pathology in estimating and staging tumor size for invasive lobular carcinoma. (ILC) group. This could be explained by a small sample size. (7) for ILC group. Conclusions: Micro-CT is a promising modality for measuring and staging the IDC.